Mohamed Kenawi & Giorgia Marchiori Unearthing Alexandria’s archaeology: The Italian Contribution - De Mitri, Carlo (Journal of Hellenistic Pottery and Material Culture, 2018)
In the studies dedicated to the Italian presences in Egypt, scholars recognize two phases of involvement, a first phase at the beginning of the nineteenth century, due mainly to political reasons and the second wave of Italian immigrants to Egypt mainly due to economic reasons. This phenomenon began in the late nineteenth century and continued until the years following the First World War and culminated in the advent of fascism.